Advancement and capacity allocation analysis of variable speed hydropower units for suppressing wind power fluctuations - Gao, Chunyang; Yu, Xiangyang; Nan, Haipeng; Zhang, Zheyuan; Wu, Luochang; Men, Chuangshe; Cai, Qingsen (Frontiers in Energy Research, 2022)
The advancement and capacity allocation of variable-speed hydropower units (VSHUs) for suppressing wind power fluctuations are studied. First, a wind–hydropower generation system model, comprising the doubly fed VSHU (DFVSHU) and full-size power VSHU (FSVSHU) is established. Then, three typical operating conditions, namely the wind speed step-up, wind speed sudden drop, and wind gust, are selected to quantify the advantages of the VSHU in suppressing wind power fluctuations using the power range, power standard deviation, and power fluctuation time. Finally, a VSHU capacity allocation scheme in which some FSHUs are transformed into VSHUs for the same total capacity of hydropower units is proposed. A VSHU capacity allocation formula based on this scheme is also proposed. Simulations and comparisons reveal that the VSHU can effectively suppress wind power fluctuations over short time scales, and its effectiveness is 90% higher than that of the FSHU. In addition, the simulation based on the measured wind speed data verifies the effectiveness of the capacity allocation formula. This study provides a new method for suppressing wind power fluctuations over short time scales and provides theoretical guidance for the application of VSHUs through capacity allocation.